Bimbingan Dan Konseling Di Madrasah Ibtidaiyyah (Paradigma Bimbingan Komprehensif dalam Bingkai Tematik-Integratif) - Muhammad Irham (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2013)
Abstract: The concept of integration in Madrasah Ibtidaiyyah (MI) not only between religion and science, but also inter-component management, teaching, and personal development. The goal is to produce graduates who are intelligent, faithful and devoted, and able to compete. However, problems of madrasa education in general and specifically MI is still confined to the graduates who are not scientists nor a scholar. Therefore, it is necessary to optimize the role of self-development component for students in basic education since or Madrasah Ibtidaiyyah. Model of self-development is the most appropriate approach to the development of integrative models-a comprehensive, unified meaning and guidance services are integrated with KBM to develop the potential of learners in a comprehensive manner. It is even stronger with the publication of the 2013 curriculum adopts a thematic-integrative. Referring to the basic strength of the curriculum in 2013 and the model with keterapaduan program guidance, energy, engineering and support system and its operation, the purpose of education to develop the whole person will be more easily achieved. Keywords: Guidance Counseling, Madrasah Ibtida’iyyah, Comprehensive.